The company's responsibility for damage and loss of passengers' baggage due to accidents from the perspective of Maslahah - Saputra, Doni; Ardiansyah, Ardiansyah (Madania: Jurnal Ilmu-Ilmu Keislaman, 2025)
This research aims to analyze the responsibility of bus companies in Medan City for damage and loss of passenger belongings due to accidents and to evaluate its alignment with the perspective of Maslahah. The issue of bus company liability is often overlooked, even though it is regulated by the Road Traffic and Transportation Law Number 22 of 2009, and the one-sided bus ticket clauses often contradict the Consumer Protection Law, thereby harming passengers. The focus of this research is to assess the extent to which the bus company's responsibilities create a sense of fairness and comfort for passengers. This research employs an empirical juridical approach, utilizing qualitative data collection methods such as interviews and document analysis. The research results show that if a bus accident occurs due to the driver's negligence, the company is obligated to replace the damaged or lost passenger belongings in accordance with the applicable regulations. However, from the perspective of Maslahah, the responsibility of bus companies in Medan City does not yet fully reflect the concept of maqashid sharia, particularly in the aspect of property preservation (hifzh al-mall). The implication of this study is the need for regulatory revisions and stricter oversight by the government to ensure that bus companies' responsibilities align with the principles of justice and welfare for public transportation users.